Asuhan Keperawatan Keluarga Tn. T Dengan Gangguan Sistem Endokrin : Diabetes Melitus di Desa Kalibuntu Kecamatan Losari Kabupaten Brebes - Vijay Maheswara; Siti Fatimah; Esti Nur Janah (STIKES Columbia Asia Medan, 2024)
Diabetes mellitus is one of th non-communicable diseases (NCDs) caused bt metabolic disorders. The purpose of this paper is to determine and provide family nursing care for Mr. T with enocrine system disorders: diabetes mellitus in Kalibuntu Village Losari District, Brebes Regency according to nursing standards. The method used is the descriptive methode in the form of interviews, observations and examinaton. From the case review, it was found that the client’s main complaint was that the client’s mai complaint was that his feet felt tingling when walking too long and there weres, GDS : 267 mg/dl. The nursing problems found were untable blood glucose levels and knowledge deficit. Intervies ere arranged and knowledge on the were unstable blood glucose levels and knowledge deficits. Interventions were arranged based on the theory in SDKI, SLKI and SIKI as well as on the client’s condition and could be implemented.